2011
DOI: 10.3109/08982104.2011.621127
|View full text |Cite
|
Sign up to set email alerts
|

N-trimethyl chitosan chloride-coated liposomes for the oral delivery of curcumin

Abstract: The aims of this study were to design the formulation of curcumin (CUR) liposomes coated with N-trimethyl chitosan chloride (TMC) and to evaluate in vitro release characteristics and in vivo pharmacokinetics and bioavailability of TMC-coated CUR liposomes in rats. The structure of synthesized TMC was examined by infrared spectroscopy, with the presence of trimethyl groups, and by proton nuclear magnetic resonance spectroscopy, indicating the high degree of substitution quaternization (65.6%). Liposomes, compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 66 publications
1
43
0
1
Order By: Relevance
“…By comparing the herbal drug-loaded systems, the SEDDS were considered to have remarkable advantages (the technology is simple and easy to direct production, higher drug loading, easy to storage in liquid and solid dosage forms) over the other formulations in deliverying herbal medicine. For example, the drug loading of curcumin in SMEDDS was 6.73 AE 0.92% , was higher than that in liposome (2.33%) (Chen et al, 2012a), triblock copolymeric micelles (6.4 AE 0.02 %) (Song et al, 2011) and gelatin microspheres (6.15 AE 0.44%) . As it described in Figure 2, SEDDS is an isotropic and thermodynamically stable solution consisting of oil, surfactant, cosurfactant and drug that can spontaneously form oil-in-water micro/nanoemulsion when mixed with water under gentle stirring.…”
Section: Introductionmentioning
confidence: 93%
“…By comparing the herbal drug-loaded systems, the SEDDS were considered to have remarkable advantages (the technology is simple and easy to direct production, higher drug loading, easy to storage in liquid and solid dosage forms) over the other formulations in deliverying herbal medicine. For example, the drug loading of curcumin in SMEDDS was 6.73 AE 0.92% , was higher than that in liposome (2.33%) (Chen et al, 2012a), triblock copolymeric micelles (6.4 AE 0.02 %) (Song et al, 2011) and gelatin microspheres (6.15 AE 0.44%) . As it described in Figure 2, SEDDS is an isotropic and thermodynamically stable solution consisting of oil, surfactant, cosurfactant and drug that can spontaneously form oil-in-water micro/nanoemulsion when mixed with water under gentle stirring.…”
Section: Introductionmentioning
confidence: 93%
“…Another study showed that curcumin incorporated into N-trimethyl chitosan chloride (TMC)-coated liposomes exhibited different pharmacokinetic parameters and enhanced bioavailability, compared with curcumin encapsulated by uncoated liposomes and curcumin suspension. Uncoated curcumin liposomes and TMC-coated curcumin liposomes showed a similar in vitro release profile [62]. In order to facilitate the intracellular delivery of curcumin, a new type of liposomes-propylene glycol liposomes (PGL) were prepared.…”
Section: Bioavailability Of Curcuminmentioning
confidence: 99%
“…Due to, mucoadhesivity, biodegradability and good antimicrobial properties of TMC, many papers focusing on this polymer have been published in the recent scientific literature reporting its biomedical applications [6][7][8][9]. Sodium alginate (ALG) is an anionic polysaccharide obtained from marine algae.…”
Section: Introductionmentioning
confidence: 99%